2013
DOI: 10.7841/ksbbj.2013.28.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of Chloroform Extract from Potentilla chinensis

Abstract: In this study, we investigated the anti-inflammation effect of Potentilla chinensis (PC) on Raw264.7 macrophage cells. Ethanol extract of PC decreased the production of nitric oxide (NO) in LPS-stimulated RAW264.7 cells. Ethanol extract was fractioned by n-hexane, chloroform, ethyl acetate, n-butanol, water and each fraction was tested for inhibitory effects on inflammation. Among the sequential solvent fractions, PC chloroform extracts (50, 100, 300, and 500 µg/mL) significantly suppressed LPS-stimulated prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
1
0
2
Order By: Relevance
“…The aerial parts of P. chinensis (Potentillae Herba) have been used in Korea as an herbal medicine against various diseases, including dysentery, hemoptysis, colitis, etc. [ 2 ]. Pharmacological studies on P. chinensis have shown that it has antioxidant, inflammatory, hypoglycemic, anticancer, and immunomodulatory properties [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aerial parts of P. chinensis (Potentillae Herba) have been used in Korea as an herbal medicine against various diseases, including dysentery, hemoptysis, colitis, etc. [ 2 ]. Pharmacological studies on P. chinensis have shown that it has antioxidant, inflammatory, hypoglycemic, anticancer, and immunomodulatory properties [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…염증반응은 우리 몸을 보호하기 위 1 한 면역체계 반응이지만 지속적인 염증반응의 진행은 세포 조직의 손상을 초래하여 암, 뇌질환, 알츠하이머병, 관절염, 천식, 염증성 장질환 및 동맥경화 등 여러 질병뿐만 아니라 노화의 직·간접적 원인이 되는 것으로 알려져 있다 [2][3][4]. 대 식세포는 염증반응에 관여하는 주요 세포로 손상 부위로의 면역세포의 이동과 Tumor necrosis factor (TNF)-α, Interleukin (IL)-1β 및 IL-6 등의 pro-inflammatory cytokine 분비에 관여 하는 등 매우 중요한 역할을 한다 [1,3,[5][6][7]. 즉, 대식세포의 사이토카인에 의한 활성화는 pro-inflammatory cytokine, Prostaglandin E2 (PGE2) 및 Nitric oxide (NO) 등을 생성함으로 써 염증성반응의 유발과 염증부위로의 면역세포의 이동을 촉진하게 된다 [1].…”
Section: Introductionunclassified
“…즉, 대식세포의 사이토카인에 의한 활성화는 pro-inflammatory cytokine, Prostaglandin E2 (PGE2) 및 Nitric oxide (NO) 등을 생성함으로 써 염증성반응의 유발과 염증부위로의 면역세포의 이동을 촉진하게 된다 [1]. 이 중 NO는 염증반응의 대표적인 지표물 질로 체내에서 NO synthase (NOS) 촉매반응을 통하여 Larginine으로부터 생성되며 [7], inducible NOS (iNOS) 및 Cyclooxygenase-2 (COX-2)가 과도하게 발현될 경우 다량의 NO를 생성하게 된다. 대식세포는 그람음성균의 세포벽을 구성하는 내독소 작용물질인 Lipopolysaccharide (LPS)의 자 극에 의해 iNOS의 발현이 급격하게 증가하는 것으로 알려져 있다 [5,6].…”
Section: Introductionunclassified